IMPLEMENTASI SISTEM INFORMASI PENGELOLAAN PELAYANAN PENDAFTARAN HAJI BERBASIS WEB MENGGUNAKAN METODE PROTOTYPE PADA PT. BANK PANIN DUBAI SYARIAH - Muhamad Dias Nur Fadilla; Hendri Ardiansyah (OKTAL : Jurnal Ilmu Komputer dan Sains, 2024)
The Hajj information and computerization system is a new form of change that is expected to be able to manage the data of pilgrims to be more optimal and efficient. With the launch of the web-based Hajj Registration Management Service System, it will make it easier and faster to provide Hajj information services. In this study the implementation of services for pilgrims through a web-based Hajj Registration Management Service System at PT. Bank Panin Dubai Syariah according to Rahma, fintech is the utilization of financial system technology that produces new products, services, technology and or business models and can have an impact on monetary stability, financial system stability, efficiency, smoothness, security and system reliability. With this Hajj registration service management application, it will greatly support the performance of managers including: 1. Marketing, 2. Branch Manager, 3. Reviewers, 4. Head of the Risk Analysis Division. With the implementation of the new system at PT. Bank Panin Dubai Syariah is able to improve performance and time efficiency in the process of verification and approval of Hajj registration at PT. Bank Panin Dubai Syariah. And the software used is the DBMS (Database Management System) which is used as the storage medium is MySQL, the programming languages PHP, JavaScript, CSS and HTML are used to create a website appearance that aims to make it easier for users or managers in the verification and approval process.